2007
DOI: 10.1038/sj.onc.1210252
|View full text |Cite
|
Sign up to set email alerts
|

Genomic profiling of malignant melanoma using tiling-resolution arrayCGH

Abstract: Malignant melanoma is an aggressive, heterogeneous disease where new biomarkers for diagnosis and clinical outcome are needed. We searched for chromosomal aberrations that characterize its pathogenesis using 47 different melanoma cell lines and tiling-resolution bacterial artificial chromosome-arrays for comparative genomic hybridization. Major melanoma genes, including BRAF, NRAS, CDKN2A, TP53, CTNNB1, CDK4 and PTEN, were examined for mutations. Distinct copy number alterations were detected, including loss o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
90
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 36 publications
11
90
1
Order By: Relevance
“…BRAF ‐subtype tumors were typically found in younger patients (Cancer Genome Atlas Network, 2015). These tumors were enriched in PTEN mutations, confirming frequent co‐occurrence of BRAF and PTEN mutations in melanoma, as shown previously (Jonsson et al ., 2007; Tsao et al ., 2012). Somatic NF1 alterations in melanoma were discovered in the early 1990s (Andersen et al ., 1993; Johnson et al ., 1993).…”
Section: Discussionmentioning
confidence: 99%
“…BRAF ‐subtype tumors were typically found in younger patients (Cancer Genome Atlas Network, 2015). These tumors were enriched in PTEN mutations, confirming frequent co‐occurrence of BRAF and PTEN mutations in melanoma, as shown previously (Jonsson et al ., 2007; Tsao et al ., 2012). Somatic NF1 alterations in melanoma were discovered in the early 1990s (Andersen et al ., 1993; Johnson et al ., 1993).…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] Additionally, both factors are overexpressed in numerous human cancers, including ovarian, cervical, pancreatic, breast, and melanoma. 9,[11][12][13][14][15][16][17][18][19] Although these studies suggest that TBX2 and TBX3 may contribute to the oncogenic process by bypassing senescence through their ability to repress common targets, whether they have redundant or distinct roles in cancers where they are both overexpressed has not yet been elucidated. Importantly, when Tbx2 function is inhibited in mouse melanoma cells lacking Tbx3, the cells senesce, 18 but whether this is possible in human melanoma cells overexpressing both proteins is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Melanomas are characterized by certain well-defined genetic alterations (reviewed in ref. 1) as well as frequent chromosomal aberrations associated with tumor progression (2). Recent work has also shown that melanomas display genomic alterations involving numerous microRNA genes (3).…”
mentioning
confidence: 99%